Pemberdayaan Petani Kopi Desa Rowosari melalui Pengendalian Hama dan Peningkatan Kualitas Tanah dengan Pupuk Organik - Nilasari Dewi; Nanang Tri Haryadi; Muhammad Firdaus; Sekar Faradita Prameswari; Rizki Amelia Rachmawati; Novia Margaretha; Aiqe Seprinanda Mubarokah; Abel Rahmad Mulyono; Hilda Ramadhani; Enjel Meylita Santosa; Erin Indriana Rosidah; Farrel Rayhan Nabil; R. Helmy Ramadianto; Ardhi Satrio Pamungkas; Fajar Kurnia Laily; Amalia Putri Sani; Azizul Nur Irza Ihtizar; Yunus Hidayat; Rachma Wahyu Hidayat; Salsabila Nur Shinta; Kurnia Hartati; Nurul Lathifa; Salsa Dinta Arizona (Institut Pertanian Bogor, 2025)
Rowosari Village, Sumberjambe Subdistrict, is one of the fostered villages of the University of Jember, where the majority of the population works as coffee farmers. However, the farmers face significant challenges in coffee cultivation due to attacks by coffee berry borer (CBB) (Hypothenemus hampei), with an infestation intensity reaching 60-67%, and nutrient deficiencies caused by the high price of fertilizers. This community empowerment program aims to address these issues through environmentally friendly pest control and soil quality improvement approaches. The solutions implemented include the application of the entomopathogenic fungus Beauveria bassiana formulation in the medium, which has been proven to reduce pest populations by up to 50%, and the use of solid organic fertilizer containing nitrogen (15%), phosphorus (0.8%), and potassium (12%). The results of this program show an increase in coffee production by 10.4% following the application of Beauveria bassiana and organic fertilizer. Farmers’ perceptions were also very positive, with a score of 4.5 out of 5 for ease of application and 4.2 for willingness to continue using the technology. Through the utilization of Beauveria bassiana and organic fertilizer in Rowosari Village, the empowerment program is expected to increase coffee productivity, improve soil conditions, and strengthen the resilience of farmers in facing pest and nutrient deficiency challenges sustainably.